An advertising campaign for the Davao branding program using tri-media - Bayang, Christine Gay D.
The Davao Branding Program (DBP), a program under the Davao City Chamber of Commerce and Industry , Inc. (DCCCII), is designed to put a brand to home grown products from Davao region. Aside from that, it helps change the attitude of the consumer towards local produce. One problem is that, the consumers do not know that a program like this exists in the region. Thus, the purpose of the program gets defeated. To address the problem, an advertising campaign was created. The advertising campaign used tri-media ? TV, radio, print ? in order to reach a larger number of consumers. In the course of the study, the AIDA Model of Advertising and the Theory of Planned Behavior helped in creating the concept for the campaign that targets the change in attitude of the consumers who were the target, the emotional appeal approach was found helpful in developing the content of the advertising campaign. As what Gary Austin (199) said, ?Successful brands has ridden on emotional strategy to the top?. From that, this advertising campaign study was able to produce a storyboard for a 45-sec TV commercial, 30-sec radio commercial and a print-ad layout for a newspaper for DBP with the theme ?Gawang Lokal, Tatak Worldclass?. It was concluded that having the consumers as the focus of the study, with the aid of the emotional appeal approach, helped in creating an effective advertising campaign.